Data Science Analytics sebagai Pendekatan Evaluasi Efektivitas Etnobook Digital terhadap Perilaku Belajar Siswa - Mohammad Yusup; Winda Erika (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
The rapid development of digital technology has encouraged the need for innovative learning media that not only improve learning outcomes but also foster students’ learning behavior. One such innovation is the Digital Etnobook, an electronic book that integrates local cultural content into the learning process. This study aims to evaluate the effectiveness of Digital Etnobook on students’ learning behavior using a Data Science Analytics approach. This research employed a quantitative approach with a descriptive–exploratory design. The research subjects consisted of 100 senior high school students, divided into two groups: an experimental group that used the Digital Etnobook and a control group that applied conventional learning methods. The data collected included pretest and posttest scores, as well as Digital Etnobook usage log data, such as duration of use, access frequency, and quiz results. Data analysis was conducted using statistical tests (paired t-test and independent t-test) and Data Science Analytics techniques based on machine learning, including Random Forest, K-Means Clustering, and Support Vector Machine (SVM). The results showed that the experimental group experienced a significantly higher improvement in learning outcomes compared to the control group. Log data analysis revealed a positive relationship between the duration of use and access frequency of the Digital Etnobook and the improvement of students’ learning outcomes. Furthermore, the applied machine learning models were able to evaluate learning effectiveness with a high level of accuracy. These findings indicate that the Digital Etnobook is effective in enhancing students’ learning behavior, and that the Data Science Analytics approach provides an objective and data-driven evaluation of learning processes. Therefore, this study concludes that the implementation of the Digital Etnobook analyzed through Data Science Analytics has the potential to serve as an innovative solution for the development of culturally based digital learning media in senior high schools in Medan.